2005
DOI: 10.1074/jbc.m412706200
|View full text |Cite
|
Sign up to set email alerts
|

The Small Heat Shock Protein IbpA of Escherichia coli Cooperates with IbpB in Stabilization of Thermally Aggregated Proteins in a Disaggregation Competent State

Abstract: The small heat shock proteins are ubiquitous stress proteins proposed to increase cellular tolerance to heat shock conditions. We isolated IbpA, the Escherichia coli small heat shock protein, and tested its ability to keep thermally inactivated substrate proteins in a disaggregation competent state. We found that the presence of IbpA alone during substrate thermal inactivation only weakly influences the ability of the bi-chaperone Hsp70-Hsp100 system to disaggregate aggregated substrate. Similar minor effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 49 publications
5
110
2
Order By: Relevance
“…41 Likewise, in E. coli the paralogs IbpA and IbpB have been shown to be incorporated into a supramolecular structure with a mass in excess of 2 MDa. 56 The rationale…”
Section: Discussionmentioning
confidence: 99%
“…41 Likewise, in E. coli the paralogs IbpA and IbpB have been shown to be incorporated into a supramolecular structure with a mass in excess of 2 MDa. 56 The rationale…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, ClpB can also assist in cooperation with DnaK/DnaJ/GrpE in ATP-driven refolding of aggregated proteins [20,22,23]. The small heat shock proteins (sHSPs) IbpA and IbpB stabilize and decrease the size of protein aggregates [24] thereby promoting DnaK/DnaJ/GrpE and ClpB mediated refolding [25] and further possible proteolysis. IB proteins are targets of these disaggregating chaperones, which remove IB material even during IB formation in a steady IB construction/deconstruction process [26,27].…”
Section: Cellular Formation Of Ibsmentioning
confidence: 99%
“…sHsps bind denatured proteins and facilitate their refolding by the ATP-dependent molecular chaperones of the Hsp70 family (Haslbeck et al, 2005). In E. coli cells, the substrates bound to IbpA/B are refolded by DnaK and its co-chaperones DnaJ and GrpE in cooperation with the AAA + protein ClpB (Veinger et al, 1998;Mogk et al, 2003a, b;Matuszewska et al, 2005). The lack of IbpA/B proteins results in increased aggregation of heat-denatured proteins in E. coli cells.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that removal of aggregated proteins at a recovery temperature of 30 u C was delayed in the absence of IbpA/B (Mogk et al, 2003a;Jiao et al, 2005). Both IbpA and IbpB are required during substrate inactivation in vitro, to efficiently stabilize denatured protein in a folding-competent state (Matuszewska et al, 2005). It is known that IbpA and IbpB interact in vitro; however, the nature of cooperation between IbpA and IbpB is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation